A convivência da enfermagem de uma unidade de cardiologia intensiva com a comunicação de notícias difíceis - Beschoren, Nagele Fatica (2018)
The communication of difficult news is part of the daily life of health professionals and is one of the most complex areas in the context of interpersonal relationships. Most of the time, the health professional is the first to know the difficult news and each one, within his field of action, will face a moment of coexistence of this type of communication during the hospitalization of the patient. The understanding of the difficult news is a continuous movement, both of the assimilation of the current situation, and of the formulation of questions. Nurses play an important role in the integrality of care, since they accompany the patient during hospitalization and it is increasingly necessary to learn to live together with the psychosocial involvement generated by the difficult news. Therefore, this research aimed to understand how the nursing of the Intensive Cardiology Unit of a teaching hospital in the interior of Rio Grande do Sul deals daily with the repercussion of the communication of difficult news to patients. The research had a qualitative, descriptive and exploratory approach. The data were obtained through a semi-structured interview with the 07 nurses of the unit. Likewise, 30-day non-participant observation of the routine work of this same team was performed in the 03 shifts of inpatient care. Content analysis was based on Bardin's proposal, following the theoretical-methodological considerations of Turato. The study concluded that although the research and literature on the role of nurses in the process of communicating difficult news are still scarce, the importance of these professionals' performance is increasingly recognized when faced with such a situation. Dealing with this type of news is a delicate task that impacts not only the patient, but also the team, which has its own reactions and sufferings. Therefore, in order to develop and improve the skills to handle the repercussions of difficult news, it is necessary to provide instruction and orientation in nursing graduation, as well as institutional spaces for sharing, reflection and continuing education.